Financial Performance of Islamic Banks in Supporting Financial System Stability in the Era of Financial Globalization - Nonik Nonik; A'nas Tasya Gusti Fiana; Delvira Nova Rosa; Sella Atviana Rohmatun; Yola Rahayu Winanti (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the financial performance of Islamic banks in supporting national financial system stability in the era of financial globalization. This research uses a descriptive quantitative approach by examining secondary data from Islamic bank financial statements during the 2019–2023 period. The analysis focuses on several financial indicators, including ROA, NPF, CAR, BOPO, and FDR. The findings indicate that Islamic banks generally show stable financial performance, supported by adequate capital, controlled financing risk, and their role in strengthening financial intermediation. These results suggest that Islamic banks have an important contribution to maintaining financial system resilience amid global financial challenges.